Node placement for wireless mesh networks: Analysis of WMN-GA system simulation results for different parameters and distributions - Barolli, Admir; Oda, Tetsuya; Ikeda, Makoto; Barolli, Leonard; Xhafa, Fatos; Loia, Vincenzo (Journal of computer and system sciences, 2015)
Wireless Mesh Networks (WMNs) are attracting a lot of attention from wireless network researchers. Node placement problems have been investigated for a long time in the optimization field due to numerous applications in location science. In our previous work, we evaluated WMN-GA system which is based on Genetic Algorithms (GAs) to find an optimal location assignment for mesh routers. In this paper, we evaluate the performance of four different distributions of mesh clients (Normal, Uniform, Exponential and Weibull) considering Packet Delivery Ratio (PDR), throughput and delay metrics. For simulations, we used ns-3 and Hybrid Wireless Mesh Protocol (HWMP) and sent multiple Constant Bit Rate (CBR) flows in the network. The simulation results show that the implemented system can be used successfully for router placement in WMNs. •We address the problem of mesh routers placement in WMNs.•The problem is formulated as a bi-objective optimization problem.•It aims to maximize network connectivity and user coverage in WMNs.•It is an NP-hard problem and is solved by a Genetic Algorithm.•The WMN-GA system can be used successfully for router placement in WMNs.